ETAs Exil in Mexiko Im Spannungsfeld der politischen Beziehungen zwischen Spanien und Mexiko (1977-2000) - Frommold, Saranda (Verlag Barbara Budrich, 2020)
Anhand einer empirischen Fallstudie wird der Konflikt zwischen Spanien und ETA aus einer transnationalen Perspektive betrachtet. Es geht darum zu zeigen, wie das Exil der ETA in Mexiko die politischen Beziehungen zwischen Spanien und Mexiko vom Etablieren des Exils ab 1977 bis zur ersten Auslieferung 2000 bestimmte und welche Rückwirkung das Thema ETA in der Außenpolitik auf den nationalen Konflikt hatte.; This case study looks at the conflict between Spain and ETA from a transnational perspective. It analyzes the exile of ETA members to Mexico as part of the foreign policy between Spain and Mexico, from the beginning of the post Franco exile in 1977 until the first extradition in 2000. In these years ETA was not only a constant topic of the bilateral agenda, but shaped decisively the development of the diplomatic relations and the national conflict itself.